2019
DOI: 10.1016/j.eururo.2019.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Primary Results from SAUL, a Multinational Single-arm Safety Study of Atezolizumab Therapy for Locally Advanced or Metastatic Urothelial or Nonurothelial Carcinoma of the Urinary Tract

Abstract: Background: Atezolizumab, a humanised monoclonal antibody targeting PD-L1, is approved for locally advanced/metastatic urothelial carcinoma. SAUL evaluated atezolizumab in a broader, pretreated population, including patients ineligible for the pivotal IMvigor211 phase 3 trial of atezolizumab. Objective: To determine the safety and efficacy of atezolizumab in an international realworld setting. Design, setting, and participants: Between November 2016 and March 2018 (median follow-up 12.7 mo), 1004 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
99
5
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 22 publications
10
99
5
3
Order By: Relevance
“…These results confirmed the tolerability of atezolizumab in a real-world, pretreated population, with similar efficacy results to the pivotal clinical trial. 141 Another smaller expanded access study of atezolizumab in patients with pretreated metastatic urothelial carcinoma reached a similar conclusion. 142 In cohort 1 of the previously mentioned IMvigor-210 trial, atezolizumab was evaluated as a first-line therapy in 119 patients with locally advanced or metastatic urothelial carcinoma who were ineligible for cisplatin.…”
Section: Atezolizumabmentioning
confidence: 77%
See 1 more Smart Citation
“…These results confirmed the tolerability of atezolizumab in a real-world, pretreated population, with similar efficacy results to the pivotal clinical trial. 141 Another smaller expanded access study of atezolizumab in patients with pretreated metastatic urothelial carcinoma reached a similar conclusion. 142 In cohort 1 of the previously mentioned IMvigor-210 trial, atezolizumab was evaluated as a first-line therapy in 119 patients with locally advanced or metastatic urothelial carcinoma who were ineligible for cisplatin.…”
Section: Atezolizumabmentioning
confidence: 77%
“…The phase IIIb SAUL study evaluated atezolizumab in 1,004 patients with pretreated, locally advanced or metastatic urothelial or nonurothelial carcinoma of the urinary tract. 141 This study sought to evaluate the safety and efficacy of atezolizumab in patients more similar to the real world population, including those ineligible for IMvigor-211. Median OS was 8.7 months (95% CI, 7.8-9.9), median PFS was 2.2 months (95% CI, 2.1-2.4), and the ORR was 13% (95% CI, 11%-16%).…”
Section: Atezolizumabmentioning
confidence: 99%
“…The median PFS of the patients in the study of De Giorgi et al, was 4.4 months (95% CI 3.7-6.2). Lastly, the study of Sternberg et al, observed no objective responses in patients with BMs from urothelial and non-urothelial urinary tract carcinoma (UTC), treated with atezolizumab 1200 mg Q3W [45]. The median PFS and OS of the patients in this study were 2.0 months (95% CI 1.5-2.3) and 3.7 months (95% CI 1.5-7.0), respectively.…”
Section: Outcomes Of Immune Checkpoint Inhibitors In Brain Metastasesmentioning
confidence: 46%
“…Zu den häufigsten behandlungsbedingten Nebenwirkungen ≥ Grad 3 zählten Asthenie, Fatigue, Kolitis und Hypertonie (mit jeweils 1 %). Die Effektivität der Behandlung war im Bereich von früheren Checkpoint-Inhibitor Studien vergleichbar [27].…”
Section: Pd-1/pd-l1-antikörper In Der Zweitlinieein Neuer Therapiestaunclassified